The Not Very Patrilocal European Neolithic Strontium, ADNA, and Archaeological Kinship Analyses. - Ensor, Bradley E. (Archaeopress, 2021)
Two decades of strontium isotope research on Neolithic European burials - reinforced by high-profile ancient DNA studies - has led to widespread interpretations that these were patrilocal societies, implying significant residential mobility for women. This volume questions that narrative from a social anthropological perspective on kinship.